Effect of Pursed lip Breathing Exercise to Reduce Dyspnea in Patient with Asthma Bronchial: Case Study - Upik Rahmi; Herry Susanto; Ewa Zuzanna Krzyż; Widiyaningsih Widiyaningsih (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
Introduction: Asthma causes chronic inflammatory disorders of the respiratory tract resulting in the narrowing of the airways so that asthmatics will complain, shortness of breath, heavy chest, and coughing, especially at night or early in the morning. One effort that can be done to overcome shortness of breath and improve oxygenation status is Pursed Lip breathing which is a non-pharmacological therapy. This case study was conducted to analyze the application of pulsed lip breathing exercises to asthmatic patients who experience shortness of breath. Method: This study used an evaluative design, namely a case study in asthmatic patients with shortness of breath. Results: After observing the administration of pulsed lip breathing exercises for three days of treatment, there were changes in respiration rate, decreased breathing, and shortness of breath. Conclusion: Pulsed lip breathing can reduce shortness of breath in asthma patients. ABSTRAKLatar Belakang: Asma menyebabkan gangguan inflamasi kronis pada saluran pernapasan sehigga terjadinya penyempitan jalan napas sehingga penderita asma akan mengeluh, sesak nafas, dada terasa berat, dan batuk-batuk terutama malam atau dini hari. Salah satu upaya yang dapat dilakukan untuk mengatasi sesak nafas dan memperbaiki status oksigenasi adalah dengan Pursed Lip breathing yang merupakan salah satu terapi nonfarmakologi. Studi kasus ini dilakukan untuk menganalisis penerapan pulsed lip breathing exercise pada pasien asma yang mengalami sesak nafas. Metode:  Penelitian ini menggunakan desain evaluatif yaitu studi kasus pada pasien  asma  dengan sesak nafas.  Hasil: Setelah dilakukan oberservasi pemberian pulsed lip breathing exercise  selama tiga hari perawatan, terdapat perubahan Respirasi rate,  pernafasan dan sesak berkurang. Kesimpulan: Pulsed lip breathing dapat mengurangi sesak napas pada pasien asma.